Aggressivity and irritability as defining features of NANDA® Labil Emotional Control diagnosis: integrative review (Research, Society and Development, 2021)
Objective: To investigate the occurrence of irritability and aggressiveness in TBI patients to, finally, conclude the relevance of these defining characteristics in the nursing diagnosis “Labile Emotional Control”, through an integrative literature review. Method: This is an integrative review from the literature that questioned this investigation: What is the evidence in relation to the defining characteristics of irritability and aggressiveness of the nursing diagnosis “Labile emotional control” in victims of traumatic brain injury? Data collection was carried out using the PUBMED and COCHRANE databases. Results: The final sample resulted in 22 articles, mostly in English as the language of publication, only two were in Spanish. The articles included were published between 1999 and 2018. Regarding the defining characteristics observed, 12 articles presented irritability as a characteristic symptom after cranioencephalic injury, 1 article presented aggressiveness as the main symptom after TBI, and 9 articles presented both symptoms correlated. Conclusion: The signs and symptoms irritability and aggressiveness as defining characteristics in the NANDA-I taxonomy, we believe to be relevant for the implementation of nursing care for patients with traumatic brain injury. Bearing in mind that this investigation must be individualized, taking into account the defining characteristics of each patient.